2020
DOI: 10.3390/cells9092130
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophils and Neutrophil Extracellular Traps Regulate Immune Responses in Health and Disease

Abstract: Neutrophils are first responders of antimicrobial host defense and sterile inflammation, and therefore, play important roles during health and disease [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 23 publications
(31 reference statements)
0
9
0
Order By: Relevance
“…Although NETs play a beneficial role in the defense of their host from pathogens, extended inflammation connected with their presence may cause a cascade of unfavorable reactions. The example of such reactions is the production of antibodies against the host’s DNA (autoimmunization), damage to surrounding tissue, or the occurrence of atherothrombotic events [ 3 , 4 , 7 , 20 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ].…”
Section: Neutrophil Extracellular Trapsmentioning
confidence: 99%
“…Although NETs play a beneficial role in the defense of their host from pathogens, extended inflammation connected with their presence may cause a cascade of unfavorable reactions. The example of such reactions is the production of antibodies against the host’s DNA (autoimmunization), damage to surrounding tissue, or the occurrence of atherothrombotic events [ 3 , 4 , 7 , 20 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ].…”
Section: Neutrophil Extracellular Trapsmentioning
confidence: 99%
“…Initially, neutrophils and NETs were considered to be involved in antimicrobials, while a number of studies had shown that they also played a pivotal role in the development of sterile inflammation under several chronic inflammatory conditions [ 42 ]. Sterile inflammation occurs in the absence of microorganisms, and it can be induced by physical, chemical, metabolic, or antigenic stimuli.…”
Section: Neutrophils and Nets In Sterile Inflammationmentioning
confidence: 99%
“…NETs are involved in the development of autoimmunity by breaking down the self-tolerance of the immune system. They may also be potentially useful as markers in order to assess the development and prognosis of autoimmune diseases (7,8). The study by Bergqvist and co-workers showed that NETs were higher in dermal tissues in the early phases of ICmediated small vessel vasculitis in hypersensitivity vasculitis and IgAV (9).…”
Section: Introductionmentioning
confidence: 99%